2008
DOI: 10.1089/neu.2008.0641
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Traumatic Brain Injury Induces a Pervasive Hyperanxious Phenotype in Rats

Abstract: Mood disturbances, including depression and anxiety disorders, are common and disabling long-term sequelae of traumatic brain injury (TBI). These psychiatric conditions have generally been considered psychosocial consequences of the trauma, but neurobiological alterations and causes have also been implicated. Using a rat model of TBI (lateral fluid-percussion injury), this longitudinal study seeks to assess anxiety and depression-like behaviors following experimental TBI. Male Wistar rats (n = 20) received a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 38 publications
5
94
2
Order By: Relevance
“…Other lateral FPI studies have also found motor, emotional, and cognitive impairments that occurred in the presence of extensive damage to the hippocampus and the frontal, parietal, and temporal cortices (Jones et al, 2008;Wahl et al, 2000). Accordingly, damage to the hippocampus and other areas may have contributed to the behavioral impairments seen in the elevated-plus maze, water maze, and beam task in the 1B7 controls.…”
Section: Behavioral Outcomesmentioning
confidence: 84%
See 1 more Smart Citation
“…Other lateral FPI studies have also found motor, emotional, and cognitive impairments that occurred in the presence of extensive damage to the hippocampus and the frontal, parietal, and temporal cortices (Jones et al, 2008;Wahl et al, 2000). Accordingly, damage to the hippocampus and other areas may have contributed to the behavioral impairments seen in the elevated-plus maze, water maze, and beam task in the 1B7 controls.…”
Section: Behavioral Outcomesmentioning
confidence: 84%
“…Previous studies have shown that decreased time spent in the open arm of the elevated-plus maze represents an increase in anxiety-like behavior (Jones et al, 2008;Walf and Frye, 2007). The 1B7 control rats spent less time in the open arm of the elevated-plus maze compared to both the sham-injured rats and CD11d mAb-treated rats at 4 weeks after the TBI, suggesting that these rats experienced heightened levels of anxiety, and that the CD11d treatment reduced the anxiogenic effect of lateral FPI.…”
Section: Behavioral Outcomesmentioning
confidence: 84%
“…Lateral FPI induces both focal and diffuse cerebral injury and is a widely accepted experimental model of moderate-to-severe human closed-head TBI (10,11). The severity of the imag-ing changes was correlated with quantitative measures of anxiety-like behavior, because mood disorders (including hyperanxiety) are common in patients after TBI, and we have demonstrated long-term increases in anxiety-like behavior in rats after FPI (7,12).…”
mentioning
confidence: 74%
“…[25][26][27][28] Briefly, anesthesia was induced with 4% isofluorane in oxygen (2 L/min) via inhalation, and maintained throughout surgery with 2% isofluorane and 500 mL/min oxygen flow delivered through a nose cone. Under aseptic conditions, rats underwent craniotomy to create a circular window (5 mm diameter) centered at A/P -3.0 mm, M/L 4.0 mm with reference to bregma to expose the dura mater.…”
Section: Lfpimentioning
confidence: 99%